Corporate Social Responsibility Management in Project Management: A Theoretical Approach - Uribe Macías, Mario Enrique (Cuadernos de Administración, 2020)
The aim of this paper is to present a theoretical approach in order to propose a social responsibility management model for project management. This theoretical support is based on the topics of Corporate Social Responsibility (CSR) and Project Management (PM). In recent times, CSR has been widely applied in permanent organizations, but there is insufficient evidence to indicate that CSR has been systematically incorporated into projects, which are temporary organizations, specifically in PM practices. The method employed began by setting the topics that should be consulted. Then, the documentary research was carried out using renowned databases and books in the two topics, based on the definition of keywords in each of them. Thereafter, the results of the research were classified by topic, and, finally, the theoretical framework was drawn up. The result revolves around items such as social responsibility, CSR, and stakeholders, as regards CSR; and revolves around the items of project and PM, as concerns PM. There is also discussion conducted based on the relationship between CSR and PM, according to the background research. The conclusions relate to the different theoretical approaches found for the concepts of CSR, project, and PM, which frame the development of research.